Groundwater quality assessment and suitability for drinking and irrigation purposes in the Jassan District, eastern Iraq - Al-Mayyahi, Sattar Obaid Maiws; Al-Zamili, Hussein Ali Awadh (Journal of Degraded and Mining Lands Management, 2026)
Sustainable development in semi-arid and dry regions relies on maintaining freshwater resources, which necessitates thoughtful management of groundwater. Groundwater quality for irrigation and drinking in the Iraqi city of Jassan was evaluated in this study using the following methods: hydrogeochemical ion analysis, water quality standard comparison, the Water Quality Index (WQI), the Pollution Index of Groundwater (PIG), the sodium absorption ratio (SAR), the residual sodium carbonate (RSC), and the sodium soluble content (Na%). Seventeen wells were used to gather the groundwater samples. The Water Quality Index (WQI) study found that groundwater in 82.4% of the study area was not fit for human consumption, with 17.6% falling into the poor category and being better suited for other uses.   According to the PIG, the majority of samples from the study area are not suitable for human consumption. Depending on where the PIG is distributed, the well samples taken from the research area indicate moderate to very high pollution levels. The SAR, RSC, and Na% values were used to assess the suitability of groundwater for agricultural use in the Jassan region. The investigation confirmed that groundwater is suitable for agricultural irrigation. Based on the findings, it is not recommended to use the city's groundwater untreated, as it is not suitable for human consumption. On the other hand, the water quality is ideal for various irrigation purposes.